ANALISIS DAYA SAING APEL TROPIS DI KOTA BATU - Agustina, Titin (Jurnal Sosial Ekonomi Pertanian, 2008)
The apple from Batu that be famous by apple batu is the special plantation from Batu City in Malang. Recently, the crop tend to decrease due to the increasing of land using movement to hausing business. The aim of the research were the to analyze the apple batu by competitive dan comparative advantages compared by import apple from overseas, to analyze the sensitivity of aplle batu caused by the changing of  the increasing of input price and decreasing of output price. Furthermore, the analyze method that used are competitive and comparative analyze that calculated by BSD, KBSD and PCR value.  The result shows that the apple batu has competitive and comparative advantages by BSD value less than the exchange rate and the KBSD and PCR value less than 1. Key word : Competitive advantage, Comparative advatage, Batu Apple